Omentin-1, a Protective Adipokine for Irritable Bowel Syndrome - Gao Y; Chen C; Huang X; Liu Y; Zhou Z; Pan Y (Journal of Inflammation Research)
Yanping Gao,1,2,* Chen Chen,1,2,* Xijing Huang,2 Ya Liu,1 Zhou Zhou,1 Yan Pan1 1Department of Gastroenterology, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 2Clinical Immunology Translational Medicine Key Laboratory of Sichuan Province, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Pan; Zhou Zhou, Sichuan Provincial People’s Hospital, 32 The First Ring Road West 2, Chengdu, Sichuan, 610072, People’s Republic of China, Email panyan2211@163.com; doublezhou2006@126.comIntroduction: Irritable bowel syndrome (IBS) is characterized by patients’ high level of suffering. There is increasing evidence for involvement of the immune system in this disease. Adipokines have been reported to be critical immunoregulators in many clinical conditions, including gastrointestinal (GI) inflammatory diseases. Our study aimed to investigate associations of omentin-1 (a newly discovered adipokine) with IBS.Methods: In the current study, serum levels of omentin-1 were measured in 209 patients with IBS (including three subtypes) and 188 healthy controls by enzyme-linked immunosorbent assay (ELISA). The somatic symptoms of IBS were determined by the 5-item IBS symptoms severity score (IBS-SSS), quality of life (QOL) by 34-item IBS-QOL questionnaire, and psychological disorders by Patient Health Questionnaire (PHQ-9), Hospital Anxiety and Depression Scale (HADS), Visceral Sensitivity Index (VSI). Therapeutic effect of omentin-1 for IBS was investigated in a 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced IBS mouse model.Results: We found that serum levels of omentin-1 were significantly decreased in patients with the diarrhea-predominant IBS (IBS-D) subtype (not the constipation or alternating subtype) compared to those in healthy subjects. Patients with lower serum omentin-1 levels suffered from higher severity of somatic symptoms (abdominal pain and distention, flatulence, rumbling), lower QOL, and worse psychological status. In a one-year follow-up, serum omentin-1 levels showed potential to reflect the disease progression. Additionally, lower omentin-1 levels were found to be accompanied with higher levels of serum pro-inflammatory cytokine concentrations in patients with IBS-D. Supplement of omentin-1 was protective against visceral hypersensitivity and mucosal inflammation in an IBS mouse model.Discussion: Our findings highlight the potential value of serum omentin-1 levels as an innovative biomarker in IBS, emphasizing its significance in improving clinical treatment and management of the disease.Keywords: irritable bowel syndrome, adipokine, omentin-1, clinical symptoms, quality of life, psychological symptoms